Practitioners' perceptions and decision‐making regarding child sexual exploitation – a qualitative vignette study. Issue 3 (29th December 2016) - Reisel, Alma
Abstract: There has been intense controversy about the appropriate response to child sexual exploitation, with debates in the UK particularly hinging on the meaning of consent and coercion. For professionals with a duty to safeguard young people from child sexual exploitation, a key site of tension is how to avoid limiting young people's experience of agency without placing them at risk. Drawing on new qualitative research findings from a vignette study designed to trace professional perception and decision‐making, this paper argues that practitioners' perceptions regarding what counts as consent are refracted through conceptions of age and choice. However, many initial perceptions of agency and its links to age were modified through the interview process. This has implications for how supervision should operate. These topics raise issues of the need for practitioners to have nuanced conceptions of consent in the context of manipulation.